Airline Jet Fuel Hedging: Theory and practice - Morrell, Peter; Swan, William (Taylor & Francis, 2006)
Most international airlines hedge fuel costs, but the theoretical justification behind this action is weak. The paper explores the nature and extent of airline fuel hedging and asks why airlines hedge. The availability of hedging instruments is first discussed, with the most liquid markets in crude and exchange traded contracts. Aviation fuel contracts are possible, but with counter-party risk. Most major passenger airlines with sufficient cash and credit now hedge at least part of their future needs. Hedging does protect profits against a sudden upturn in crude prices caused by political and consumer uncertainty leading to slower economic growth. However, if higher oil prices are induced by strong economic growth and oil supply constraints, hedging increases volatility with hedging gains reinforcing improved profits from higher traffic and improved yields. If hedging does not reduce volatility, it may still have an accounting role in moving profits from one time period to another, insure against bankruptcy, and signal the competence of management to investors and other stakeholders.